The Unprivileged Modern Exile: From Nostalgia to Antinostalgia and Beyond - Vaso, Jora (Archiwum Emigracji, 2021)
THE UNPRIVILEGED EXILE: FROM NOSTALGIA TO ANTINOSTALGIA AND BEYOND “Nostalgia,” writes Antonio Prete, quoting Niccolò Tommaseo, “is the noble privilege of poor countries.” Though both exile and nostalgia may befall those from more affluent countries and cultures, the conditions are noble and privileged only for those who hail from poor countries which, as Witold Gombrowicz states when referring to Poland, have “a minor role,” are doomed to imperfection, and produce less sophisticated men. Polish poet Zbigniew Herbert and Albanian poet Gëzim Hajdari share a similar fate to that of Gombrowicz as they both struggle with the inherent inferiority of their birthplaces and, consequently, experience difficulties in finding a clear position in a globalised world. With very few exceptions, the level of development or affluence of a certain country is closely linked to the nostalgic or antinostalgic feelings experienced by the exiles with both feelings experienced by people from poorer countries. The rise of antinostalgic exiles in the 20th century, like Witold Gombrowicz, Henryk Grynberg, and Gëzim Hajdari, as well as in the 21st century may be an indication of the future of nostalgia or, more specifically, the new face of nostalgia. NIEUPRZYWILEJOWANE WYGNANIE: OD NOSTALGII DO ANTYNOSTALGII Niccolò Tommaseo powiedział, że nostalgia jest szlachetnym przywilejem biednych krajów. Chociaż wygnanie i nostalgia mogą spotkać tych z zamożniejszych krajów i kultur, w których są dobre warunki do życia, jednak wspomniane uprzywilejowanie jest tylko dla tych, którzy pochodzą z biednych krajów. Witold Gombrowicz, rozpatrując to zagadnienie w polskim kontekście, zauważa, że ludzie z tych krajów mają „niewielkie możliwości”; są skazani na niedoskonałość, ponieważ istniejąca w tej przestrzeni rzeczywistość kształtuje mniej wyrafinowanego człowieka. Zbigniewa Herberta, polskiego poetę, i jego albańskiego kolegę po piórze Gëzima Hajdariego łączy z Gombrowiczem podobny los. Zmagają się z wrodzonym poczuciem niższości miejsca swego urodzenia. Mają tym samym trudności z odnalezieniem i określeniem, jako twórcy, swego miejsca w sensie globalnym. Poziom rozwoju lub zamożności danego kraju, z nielicznymi wyjątkami, jest ściśle związany z nostalgicznym lub antynostalgicznym odczuwaniem wygnania. A to oznacza, że wskazane doznania są doświadczeniem ludzi z biedniejszych krajów. Funkcjonowanie w XX i XXI wieku antynostalgicznych wygnańców takich jak Witold Gombrowicz, Henryk Grynberg i Gëzim Hajdari, może świadczyć o przyszłości nostalgii, a ściślej mówiąc — współczesnego oblicza nostalgii.